Faktor yang Mempengaruhi Bendungan ASI pada Ibu Nifas di RSUD K.R.M.T. Wongsonegoro Semarang - Siti Nafara Kamelia; Niken Sukesi (Lembaga Pengembangan Kinerja Dosen, 2025)
Breast milk damming is the result of inadequate emptying and delayed milk ejection, which blocks the glands and causes the milk to get dammed. Breast milk dam events are brought on by a build-up of breast milk and inadequate milk ejection, which obstructs the milk ducts and produces breast enlargement. The purpose of this study is to examine the variables that affect postpartum women's breast milk dams. This study's methodology combines a cross-sectional approach with analytical survey research to get quantitative results. Respondents were given a questionnaire form to complete in order to collect data. The research sample used a total sampling of 37 respondent. Total sampling was used to determine sampling. Data were analyzed using Chi-square test with the help of Fisher’s exact test and Likelihood ratio. The results of the research in this study showed that all variables influenced breast milk dam by obtaining a p value <0.05. Bivariate analysis on breastfeeding position found P = 0.012 which means there is an effect of breastfeeding position on breast milk dam. In breast care, the value of p=0.001 was obtained which has an influence on breast milk dam. While the frequency of breastfeeding has an effect on breast milk dam with a value of p=0.000. And in knowledge with a value of p=0.009 which means it has an influence on breast milk dams. It was concluded that there was an influence of breastfeeding position, breast care, breastfeeding frequency, and knowledge on breast milk dams. The most influential factor on breast milk dam is the breast care variable.